Pendampingan Anak dalam Lembaga Kesejahteraan Sosial Panti Asuhan Darussalam dalam Membuat Usaha Warung Kopi dan Cucian Sepeda Motor di Tegal Mulyorejo Baru Surabaya - Sutono Sutono; Akmad Kusnan Arif (Nusantara Mengabdi Kepada Negeri, 2024)
This service is entitled assisting children in the Darussalam orphanage social welfare institution in creating a coffee shop and motorbike washing business in Tegal Mulyorejo Baru Surabaya. The problems that the author raises are: What is the process of implementing child mentoring at the Child Welfare Institution at the Darussalam Orphanage in Mulyosari Baru Surabaya, What are the results of implementing child mentoring at the Darussalam Orphanage Social Welfare Institution in Mulyosari Baru Surabaya, What is the process of mentoring for the creation of a coffee shop and motorbike wash? at the Darussalam orphanage social welfare institution in Mulyorejo Baru Surabaya. The method used is a qualitative method with data collection through observation, interviews and documentation; With this method, the author can provide good mentoring results, including the development of the creativity of Darussalam orphan children in creating coffee shops and motorbike washes, the totality of each child in running a coffee shop and motorbike wash business.